LEARNING THEORIES AND THEIR APPLICATION IN THE CONTEXT OF PROGRAMMING LANGUAGES (Web of Technology: Multidimensional Research Journal, 2024)
This article analyzes the theories of learning - behaviorism, cognitivism and constructivism and their application in teaching programming languages. On the basis of these theories, scientific applications of software tools and methods for effective organization of the educational process are considered. It also provides information about the possibilities of developing students' algorithmic thinking skills through programming languages and modern platforms used to automate such a process. Scientific and practical foundations are explored, and theoretical approaches are shown in practice.